Neural Correlates of Auditory Verbal Hallucinations in Schizophrenia and the Therapeutic Response to Theta-Burst Transcranial Magnetic Stimulation. (3rd May 2018) - Chen, Xingui; Ji, Gong-Jun; Zhu, Chunyan; Bai, Xiaomeng; Wang, Lu; He, Kongliang; Gao, Yaxiang; Tao, Longxiang; Yu, Fengqiong; Tian, Yanghua; Wang, Kai
Abstract: Auditory verbal hallucinations (AVHs) are a core symptom of schizophrenia, and resistant to antipsychotic medication in a substantial proportion of patients. This study aimed to investigate the neural correlates of AVHs in schizophrenia patients and its response to a modified continuous theta-burst stimulation (cTBS) by transcranial magnetic stimulation. In a cross-sectional experiment, resting-state functional magnetic resonance images were collected from 31 AVH schizophrenia patients, 26 non-AVH schizophrenia patients, and 33 sex-/age-matched healthy controls (HCs). Functional connectivity strength (FCS) maps were compared among groups by 1-way analysis of variance (ANOVA). In a longitudinal experiment, 16 and 11 AVH patients received real and sham cTBS treatment for 15 days, respectively. Notably, this was not a randomized control trail. Changes in AVH and FCS were analyzed by 2-way ANOVA and 2-sample t -test, respectively. In the cross-sectional experiment, comparison of FCS maps identified 8 clusters among groups, but only one cluster (in left cerebellum) differed significantly in AVH patients compared to both HCs and non-AVH patients. In the longitudinal experiment, the real cTBS group showed a greater improvement in symptoms and a larger FCS decrease in left cerebellum than the sham group. Pearson's correlation analysis indicated that baseline FCS of the overlapping cerebellum cluster (between the cross-sectional and longitudinal findings) was negatively correlated with symptom improvement in the real treatment group. These findings emphasize the role of the left cerebellum in both the pathophysiology and clinical treatment of AVHs in schizophrenia patients.